1989
DOI: 10.1007/bf01856024
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intracoronary diltiazem on regional myocardial function and development of infarcts in porcine hearts

Abstract: The effect of intracoronary (i.c.) pretreatment with diltiazem on regional myocardial function and the development of infarcts was investigated in regionally ischemic, reperfused porcine hearts. The left anterior descending coronary artery (LAD) was distally ligated in 16 pigs for 20-90 min followed by 24 h of reperfusion. Eight pigs were treated with increasing doses of i.c. diltiazem (0.375 mg/min, 0.75 mg/min, 1 mg/min) prior to ischemia. Eight pigs served as controls. Regional myocardial function was asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
1995
1995

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…The risk region could accurately be delineated by an injected dye because porcine hearts lack significant collateral blood flow [19,20], warranting a clear and sharp border between ischemic and well-perfused myocardium. Ischemia of 75 minutes (series A) was chosen because experiments with ]C diltiazem had suggested that infarct sizes of 40% to 60% could have been expected in this group [21], allowing the assessment of smaller or larger infarctions in the other treatment groups. In series B, the LAD was occluded for 45 minutes since mean infarct sizes of 70% to 75% were obtained in previous control experiments [9,10].…”
Section: Applied Methodsmentioning
confidence: 99%
“…The risk region could accurately be delineated by an injected dye because porcine hearts lack significant collateral blood flow [19,20], warranting a clear and sharp border between ischemic and well-perfused myocardium. Ischemia of 75 minutes (series A) was chosen because experiments with ]C diltiazem had suggested that infarct sizes of 40% to 60% could have been expected in this group [21], allowing the assessment of smaller or larger infarctions in the other treatment groups. In series B, the LAD was occluded for 45 minutes since mean infarct sizes of 70% to 75% were obtained in previous control experiments [9,10].…”
Section: Applied Methodsmentioning
confidence: 99%